Crosstalk of nervous and immune systems in pancreatic cancer - Huang, Fei-Fei; Cui, Wen-Hui; Ma, Lan-Yue; Chen, Qi; Liu, Yang (Frontiers in Cell and Developmental Biology, 2023)
Pancreatic cancer is a highly malignant tumor known for its extremely low survival rate. The combination of genetic disorders within pancreatic cells and the tumor microenvironment contributes to the emergence and progression of this devastating disease. Extensive research has shed light on the nature of the microenvironmental cells surrounding the pancreatic cancer, including peripheral nerves and immune cells. Peripheral nerves release neuropeptides that directly target pancreatic cancer cells in a paracrine manner, while immune cells play a crucial role in eliminating cancer cells that haven't evaded the immune response. Recent studies have revealed the intricate interplay between the nervous and immune systems in homeostatic condition as well as in cancer development. In this review, we aim to summarize the function of nerves in pancreatic cancer, emphasizing the significance to investigate the neural-immune crosstalk during the advancement of this malignant cancer.